The Influence Of The Application Of The Show And Tell Learning Method On The Expressive Language Skills Of Children Aged 5-6 Years - Husain, Tri Alfira; Bachtiar, Muhammad Yusri; Dzulfadhilah, Fitriani; Amriani H, Sri Rika (As-Sibyan: Jurnal Pendidikan Anak Usia Dini, 2025)
The Influence Of The Application Of The Show And Tell Learning Method On The Expressive Language Skills Of Children Aged 5-6 Years. This study examines the urgency of developing aspects of language in early childhood, especially expressive language skills through the application of the show and tell learning method in children aged 5-6 years. The purpose of this study was to examine the effect of the application of the show and tell learning method on the expressive language skills of children aged 5-6 years at Kemala Bhayangkari 07 Gowa Kindergarten. The approach used in this research is a quantitative approach with a quasi-experimental type of research. The design used is a non-equivalent control group design. The data collection techniques used are observation, documentation, and also tests. The sampling technique used was purposive sampling consisting of 14 children in the experimental group and 14 children in the experimental group. The data analysis technique used is descriptive statistical analysis and non-parametric analysis using the Wilcoxon Sign-Rank Test. Based on the results of the data analysis conducted, Asymp. (2-tailed) = 0.001 <0.05 was obtained, so H1 was accepted and H0 was rejected. there is a significant effect of the application of the show and tell learning method on the expressive language skills of children aged 5-6 years at Kemala Bhayangkari 07 Kindergarten.